Om allokering av straffansvar vid arbete utan tillstånd - Heikki Kallio (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract On 23 February 2023, a comprehensive reform of the Aliens Act concerning the employment and business activities of foreign nationals entered into force in Finland. The objective of the reform was to increase the authorities’ ability to prevent the exploitation of foreign labour. One of the most significant changes involved the client´s obligations to ensure the right to work for foreign nationals entering and remaining in employment. These changes were prompted by, among other things, problems identified in the regulatory framework concerning the obligations of the employer and the client and the allocation of criminal liability.